FRIENDSHIP IN A COLLECTION OF SUPERMAN IS DEAD LYRICS: FRIENDSHIP IN A COLLECTION OF SUPERMAN IS DEAD LYRICS - Mubarok, Insani Wahyu (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2023)
Friendship relations are one of the efforts to fulfill social-emotional needs for individuals, especially for adolescents. Simultaneously with the entry of adolescence, according to the theory of psychosocial stages. An individual is faced with the task of developing identity versus role confusion. Dumas: 2012 states that during adolescence, adolescents spend a lot of time interacting in peer groups. Superman Is Dead (abbreviated as SID) is a punk rock band from Bali, Indonesia, based at Poppies Lane II, Kuta. This music group consists of three youths from Bali, namely: vocalist Bobby Kool, bassist Eka Rock and drummer Jerinx. In the lyrics above Superman is dead conveys a message to listeners that "a handful of hope" every friend has hopes and hopes can be interpreted as ideals that must be pursued. “Takkan pernah menyerah, terus kubertahan” It can be concluded that the lyrics of the Superman Is Dead song are closely related to friendship relations, namely the existence of motivation between friends, the existence of solidarity between friends, solidarity, disappointment and conflict between friends. Keywords: Song Lyrics, Superman Is Dead, Friendship Relations